Speech and language therapy interventions for children with primary speech and/or language disorders - Law, James (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To determine the effectiveness of speech and language therapy interventions for children with a primary diagnosis of speech and/or language disorders. The review will focus on comparisons between active interventions and controls.